Security Services Measures of Secret Data Compiling – Comparative Legal Approach - Mirković, Vladan M (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
Security services as specialized state bodies represent an important part of any national security system and as such bear the responsibility for achieving overall security. In carrying out their activities and tasks, they are authorized to apply different measures and methods and the most effective are measures for secret data compiling. Although effective, their prescription and application are always sensitive, since they are measures that deviate more or less from guaranteed human rights, above all the right to privacy and the right to secrecy of communication. After the attacks on New York and Washington on September 11, 2001, “the war on terror” and in general the activities on the achieving of national security have often been marked by violations of human rights under the pretext of protecting the public interest and national security. In order to prevent the measures and activities in the realization of national security from turning into terrorism and state terror, the Council of Europe and European Union have adopted certain rules which states members should adhere to when prescribing and implementing measures of secret data compiling in order to achieve an important goal - to respect the standards of the rule of law, thus safeguarding public and private interests equally. Analysis of the security service’s measures of secret data compiling for preventive purposes in this paper include legal solutions in Slovenia, Croatia, Bosnia and Herzegovina and Montenegro.